Antitumor Necrosis Factor-like Ligand 1A Therapy Targets Tissue Inflammation and Fibrosis Pathways and Reduces Gut Pathobionts in Ulcerative Colitis. Issue 3 (24th August 2021) - Hassan-Zahraee, Mina; Ye, Zhan; Xi, Li; Baniecki, Mary Lynn; Li, Xingpeng; Hyde, Craig L; Zhang, Jenny; Raha, Nancy; Karlsson, Fridrik; Quan, Jie; Ziemek, Daniel; Neelakantan, Srividya; et al.
Abstract: Background: The first-in-class treatment PF-06480605 targets the tumor necrosis factor-like ligand 1A (TL1A) molecule in humans. Results from the phase 2a TUSCANY trial highlighted the safety and efficacy of PF-06480605 in ulcerative colitis. Preclinical and in vitro models have identified a role for TL1A in both innate and adaptive immune responses, but the mechanisms underlying the efficacy of anti-TL1A treatment in inflammatory bowel disease (IBD) are not known. Methods: Here, we provide analysis of tissue transcriptomic, peripheral blood proteomic, and fecal metagenomic data from the recently completed phase 2a TUSCANY trial and demonstrate endoscopic improvement post-treatment with PF-06480605 in participants with ulcerative colitis. Results: Our results revealed robust TL1A target engagement in colonic tissue and a distinct colonic transcriptional response reflecting a reduction in inflammatory T helper 17 cell, macrophage, and fibrosis pathways in patients with endoscopic improvement. Proteomic analysis of peripheral blood revealed a corresponding decrease in inflammatory T-cell cytokines. Finally, microbiome analysis showed significant changes in IBD-associated pathobionts, Streptococcus salivarius, S. parasanguinis, and Haemophilus parainfluenzae post-therapy. Conclusions: The ability of PF-06480605 to engage and inhibit colonic TL1A, targeting inflammatory T cell and fibrosis pathways, provides the first-in-human mechanistic data to guide anti-TL1A therapy for the treatment of IBD. Graphical Abstract: